Book Reviews (The ecumenical review, 1962)
Book reviewed in this article: THE ECUMENICAL MOVEMENT: Christliche Einheit und Ökumenische Bewegung, by Charles Boyer THE ECUMENICAL MOVEMENT: The Loss of Unity, by Hoffman Nickerson THE ECUMENICAL MOVEMENT: The Quest for Church Unity, by Matthew Spinka PREPARATION FOR DIALOGUE: Eastern Christendom, by Nicolas Zernov PREPARATION FOR DIALOGUE: Religion in the Soviet Union, by Walter Kolarz PREPARATION FOR DIALOGUE: La Vie religieuse en URSS, by Constantin de Grunwald PREPARATION FOR DIALOGUE: L'Eglise orthodoxe, by Olivier Clément PREPARATION FOR DIALOGUE: A Commentary on the Divine Liturgy, by Nicolas Cabasilas PREPARATION FOR DIALOGUE: Saint Grégoire de Nazianze, edited by Edmond Devolder PREPARATION FOR DIALOGUE: Saint Irénée, by André Benoit PREPARATION FOR DIALOGUE: Gnosis, La tradition ésotérique de l'Orthodoxie orientale, by Boris Mouravieff PREPARATION FOR DIALOGUE: Theological Study in the Rumanian Orthodox Church under Communist Rule, by A. Johansen PREPARATION FOR DIALOGUE: Der Primat des Petrus in der Orthodoxen Kirche, by A. Afanassieff, N. Koulomzine, J. Meyendorff, A. Schmemann PREPARATION FOR DIALOGUE: A Patristic Greek Lexicon, edited by G. W. H. Lampe THE PRESBYTERIAN WAY: The presbyterian Way of Life, by John A. Mackay THE PRESBYTERIAN WAY: The Coming Reformation, by Geddes MacGregor THE PRESBYTERIAN WAY: Von der Reformation zum Morgen, edited by Josef L. Hromadka THE PRESBYTERIAN WAY: Le Catéchisme de Heidelberg: un Commentaire pour notre Temps, by André Péry THE PRESBYTERIAN WAY: San Paulo Dokumente, by Focko Lüpsen THE PRESBYTERIAN WAY: Calvin Bibliographie, 1901–1959, by Wilhelm Niesel THE CHURCH FACING SOCIAL QUESTIONS: Kontinente wachsen zusammen, edited by K. von Bismark and F. Karrenberg THE CHURCH FACING SOCIAL QUESTIONS: Das Diakonische Amt der Kirche im œkumenischen Bereich, edited by Herbert Krimm FREEDOM FOR THE CHURCH: Struggle for Freedom. History of the Philippine Independent Church, by Lewis Bliss Whittemore FREEDOM FOR THE CHURCH: Religious Revolution in the Philippines, by Pedro S. de Achutegui, s.j. and Miguel A. Bernad FREEDOM FOR THE CHURCH: Das Dilemma der Volkskirche, by Georg F. Vicedom FREEDOM FOR THE CHURCH: The German Phoenix, by Franklin Hamlin Littell FREEDOM FOR THE CHURCH: The Anabaptist View of the Church, by Franklin Hamlin Littell FREEDOM FOR THE CHURCH: Wesley's Christology, by John Deschner FREEDOM FOR THE CHURCH: The role of the district Superintendent in the Methodist Church, by Murray H. Leiffer FREEDOM FOR THE CHURCH: What Churches of Christ stand for, by William Robinson FREEDOM FOR THE CHURCH: Towards Christian Union, edited by James Gray FREEDOM FOR THE CHURCH: We were brought together, report of the National Conference of Australian Churches, edited by David M. Taylor FREEDOM FOR THE CHURCH: Ancient, Medieval and Modern Christianity. The Evolution of a Religion, by Charles Guignebert GREEK THEOLOGY GERMAN THEOLOGY: Aus der neugriechischen Theologie, edited by Demosthenes Savramis GREEK THEOLOGY GERMAN THEOLOGY: Textbuch zur deutschen systematischen Theologie und ihrer Geschichte vom 16. bis 20. Jahrhundert GREEK THEOLOGY GERMAN THEOLOGY: Vol. 2, 1934–1960, begun by Richard H. Grützmacher